Anthropogenic Decline of Ancient, Sustainable Water Systems: Qanats. Issue 1 (5th September 2022) - Maghrebi, Mohsen; Noori, Roohollah; Sadegh, Mojtaba; Sarvarzadeh, Fereshteh; Akbarzadeh, Aliasghar Erfanian; Karandish, Fatemeh; Barati, Reza; Taherpour, Hamid
Abstract: Qanat is an ancient underground structure to abstract groundwater without the need for external energy. A recognized world heritage, Qanat has enabled civilization in arid and semi‐arid regions that lack perennial surface water resources. These important structures, however, have faced significant challenges in recent decades due to increasing anthropogenic pressures. This study uses remote sensing to investigate land‐use changes and the loss of 15, 983 Qanat shafts in the Mashhad plain, northeast of Iran, during the past six decades. This entails obtaining a rare aerial imagery from 1961, as well as recent satellite imagery, over a region with the highest density of Qanats in Iran, the birthplace of Qanat. Results showed that only 5.59% of the Qanat shafts in 1961 remained intact in 2021. The most prominent Qanat‐impacting land‐use changes were agriculture and urban areas, that accounted for 42.93 and 31.81% Qanat shaft destruction in the study area, respectively. This study also showed that groundwater table decline, demographic changes, and reduction in the appeal of working in the Qanat maintenance and construction industry among the new generation are existential threats to Qanats, and may result in the demise of these ancient structures in the future. Findings of this study can be used for urban planning in arid and semi‐arid areas with the aim of protecting these historic water structures. Abstract : Article impact statement : Qanats are historical, sustainable groundwater abstraction infrastructure that face an existential threat from anthropogenic pressures.